Including students as co-enquirers: Matters of identity, agency, language and labelling in an International participatory research study. (2017) - Gibson, Suanne; Baskerville, Delia; Berry, Ann; Black, Alison; Norris, Kathleen; Symeonidou, Simoni
Highlights: The complexities of participatory research methodology. Participants as co-researchers. Agency and clarifying roles in research. Communication and language in research. Research for inclusion and diversity. Abstract: This paper takes the reader through the methodological development of an international study, which involved 8 academics and 373 students in Departments of Education from 6 universities in Europe, New Zealand and the USA. It explores the uses, benefits and critical tensions within participatory research methodology when used in a study addressing questions of undergraduate student diversity and inclusion. Issues when linking the views and interests of the various project parties, a core element of participatory research, are considered. Alongside this is a discussion on how this led to shifts in participant role identities, a reconfiguration of research ownership and insights into the complexities of participants' education. The work addresses a niche area in terms of participants as co-researchers, in particular matters of identity, agency, language and labelling, thus adding to developments in this field.